Antibacterial activity of Synsepalum dulcificum leaf extract against Listeria monocytogenes and its comparison with Strobilanthes crispus and Morus alba - Wasoh, H; Tajuddin, S; Halim, M; Mohd Hairul, AR; Sobri, MZM; Lajis, AFB; Yusof, MT; Ariff, AB (Journal of Bio-Science, 2018)
Abstract not available J. bio-sci. 25: 73-75, 2017